Problems Of Organization Of Management Accounting In Water Construction Organizations And Solutions - Gafurova Shahlo Daniyarovna (Peerian Journals Publishing, 2022)
The article highlights the shortcomings and problems in the organization of management accounting, ways to solve these problems, as well as issues of improving the organization of management accounting, and studies the theoretical, practical and methodological aspects of management accounting. Errors and omissions in the organization of management accounting are considered, the main requirements for the formation of management reports in water management companies, the financial and economic activities of the business entity, which determines the management accounting system
Keywords: management accounting; management accountingwater economy construction; budgeting